dara 3.0/3.1 - Was hat sich bei der DOI-Registrierung für Sozial- und Wirtschaftsdaten geändert? - Brigitte Hausstein; Ralf Toepfer (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2014)
– dara operates as the registration agency for social science and economic data jointly run by GESIS (http://www.gesis.org) and ZBW (http://www.zbw.eu). dara pursues the goal of long-term, persistent identification and availability of research data via allocation of DOI names. In keeping with the ideals of good scientific practice there is a demand for open access to existing primary data so as to not only have the final research results but also be able to reconstruct the entire research process. GESIS and ZBW therefore offer a registration service for social and economic research data in cooperation with DataCite (http://www.datacite.org), an international consortium pursuing the goal of supporting the acceptance of research data as independent citable scientific objects. This infrastructure lays the foundation for long-term, persistent identification, storage, localization and reliable citation of research data. [...]
Keywords: 330